Effect of Conbercept Treatment on Macular Edema and Microvascular Structure in Eyes with Retinal Vein Occlusions - Ding X; Wang Y; Zou B; Zang D; Hao Y (International Journal of General Medicine, 2022)
Xiaoxia Ding, Yu Wang, Bo Zou, Dongxiao Zang, Yi Hao Department of Ophthalmology, Fushun Eye Hospital, Fushun, Liaoning, People’s Republic of ChinaCorrespondence: Xiaoxia Ding, Fushun Eye Hospital, No. 1 Hupo Street, Xinfu District, Fushun, 113008, People’s Republic of China, Email 791151967@qq.comObjective: To evaluate the efficacy on best corrected visual acuity (BCVA) and microvascular structure changes of conbercept intravitreal injection for the treatment of macular edema (ME) secondary to different types of retinal vein occlusion (RVO) and to explore the baseline OCTA parameters which were related to the change of BCVA and CRT after the intravitreal conbercept injection to RVO.Methods: A retrospective observational study was conducted involving 67 eyes from 67 patients who were diagnosed with ME secondary to RVO between April 2019 to December 2020. The subjects were divided into branch retinal vein occlusion (BRVO) and central retinal vein occlusion (CRVO) according to the involved vessel, subsequently the subjects received intravitreal conbercept treatment. The BCVA and fundus microstructure were measured to identify predictors of effective outcomes.Results: BCVA, central retinal thickness (CRT), fovea avascular zone (FAZ), and foveal vascular density (FVD) in superficial capillary plexus (SCP) were significantly changed from baseline to 6-month follow-up in both CRVO and BRVO. In the BRVO group, age and baseline BCVA were correlated with changes of BCVA, while the baseline CRT, FVD in the DCP, and parafovea vascular density (PFVD) in DCP were associated with changes of CRT (P< 0.05). In the CRVO group, the baseline BCVA was correlated with changes of BCVA, while age, gender, baseline CRT, FVD in DCP, and PFVD in DCP were associated with changes of CRT (P< 0.05). There were no serious adverse events (SAEs) related to the drug or the injection procedure.Conclusion: Intravitreal injections of conbercept can improve BCVA and CRT and change the FVD in SCP effectively both in BRVO and CRVO groups. In addition, the baseline FVD and PFVD in the DCP were related to the change of CRT after intravitreal conbercept treatment.Keywords: conbercept, retinal vein occlusion, macular edema, microvascular structure, best-corrected visual acuity